VIOLATIONS AND ABUSES IN THE MANAGEMENT OF FINANCIAL RESOURCES AT THE LOCAL LEVEL IN CONDITIONS OF DECENTRALIZATION (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The initiated processes of reforming the government and public finances in Ukraine have provided real opportunities for increasing the resources of sustainable development of economic systems at different levels, especially the basic ones. At the same time, as practice shows, the deepening of the processes of financial decentralization causes the emergence of financial irregularities and abuses at different levels of local financial management, which ultimately does not allow to achieve the set goals. These aspects actualize the increased interest in the scientific and practical problem of detecting financial irregularities and abuse in managing local finances.The purpose of the article is to identify the main forms of abuse and irregularities that arise at different levels of local financial management in the process of implementing decentralization reform and outlining the directions for their elimination.Methods of system-structural and functional analysis were used in the study of local financial management processes.The peculiarities of financial resources management in the context of administrative-territorial units in the process of implementation of the decentralization reform on the example of Cherkasy, Poltava, Vinnytsia, and Kirovograd regions are revealed. The main forms of violations were identified, namely: misuse of budget funds; borrowing by budgetary institutions contrary to the BCU (oblast); lack of a systematic approach to planning the need for budgetary funds (including education, health, and social protection); dispersion of funds between different programs; decision making not supported by financial resources (cities); ineffective decisions regarding the allocation of intergovernmental transfers (in the field of OZ) low level of control over the use of land resources by local authorities; loss of opportunities to mobilize financial resources (districts); low budget planning and administration of local taxes and fees; formal planning of the socio-economic development of the UGT and financing of measures for its implementation (villages, UGT). Based on the results of the research, recommendations were made to reduce financial abuse and abuse by local governments.
Keywords: abuse, abuse, financial resources, local budgets, decentralization